2015
DOI: 10.1016/j.teac.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Position paper on passive sampling techniques for the monitoring of contaminants in the aquatic environment – Achievements to date and perspectives

Abstract: Highlights:-Monophasic polymer PS are recommended for hydrophobic substances.-Adsorption-based PS for hydrophilic substances provide semi-quantitative data.-The development of new PS for ionic and highly hydrophilic substances is required.-PS reflect the contaminant levels to which biota is exposed in waters.-PS allow to rank areas with risk of EQS exceedance before monitoring in biota. Highlights:-Monophasic polymer PS are recommended for hydrophobic substances.-Adsorption-based PS for hydrophilic substances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…The recently organised NORMAN/AQUAREF workshop on passive sampling techniques for monitoring of contaminants in the aquatic environment [24] concluded that currently, the mechanisms of uptake to adsorption based PS are neither completely understood, nor fully under control. The calibration data that are available from literature are often variable and (unlike in partitioning PS) very substance specific [25].…”
Section: Availability Of Accurate Calibration Data For Adsorption Basmentioning
confidence: 99%
“…The recently organised NORMAN/AQUAREF workshop on passive sampling techniques for monitoring of contaminants in the aquatic environment [24] concluded that currently, the mechanisms of uptake to adsorption based PS are neither completely understood, nor fully under control. The calibration data that are available from literature are often variable and (unlike in partitioning PS) very substance specific [25].…”
Section: Availability Of Accurate Calibration Data For Adsorption Basmentioning
confidence: 99%
“…This calibration in combination with knowledge of the accumulation mechanisms of passive samplers allows the estimation of time-weighted average (TWA) water concentrations. However, the mechanisms of accumulation and desorption of polar contaminants into passive samplers are still not fully understood (Miège et al 2015), particularly for short durations (<1d). To date, contaminant concentrations in sewer overflows have mainly been monitored with traditional sampling methods such as grab samples and auto-samplers which have their short-comings.…”
Section: Introductionmentioning
confidence: 99%
“…The Chemcatcher® sampler (Kingston et al 2000) is one of two common designs used to sample polar organic contaminants (Miège et al 2015). For the monitoring of short duration pollution events, suggested the use of styrenedivinylbenzene reverse phase sulfonated disks (SDB-RPS) without polyethersulfone (PES) membrane to obtain a high mass uptake of the passive samplers.…”
Section: Introductionmentioning
confidence: 99%
“…Passive sampling techniques have become popular for the monitoring of organic compounds present in aquatic systems (Chen et al 2013, Chen et al 2015b, Miège et al 2015, Mills et al 2014, Mills et al 2007, Vrana et al 2005) since first introduced in the 1980s (Soedergren 1987).…”
Section: Introductionmentioning
confidence: 99%